Incorporating annoyance in airport environmental policy: Noise, societal response and community participation - Suau-Sanchez, Pere; Pallares-Barbera, Montserrat; Paül, Valerià (Elsevier Science B.V., Amsterdam., 2011)
Airport capacity continues to be one of the air transport issues that creates the most concern. The major environmental constraint for airports is the noise generated by aircraft. Annoyed communities living around airports have become a limiting factor for airport capacity and operability. This paper brings together the existing literature in the fields of airport environmental capacity, non-acoustic factors of noise annoyance, NIMBYism and environmental conflicts. We also analyze the socio-environmental conflict between Barcelona airport and the community of Gaya Mar. This case shows that the lack of trust between parties, the impossibility of predicting noise exposure, the absence of opportunities for civil society to speak and the difficulty of accessing relevant information foster annoyance and mobilization in the communities that live around the airport. In addition, it is shown that, in such a situation, communities' reactions can evolve to a post-NIMBY stage in which proactive attitudes replace reactive ones. (C) 2010 Elsevier Ltd. All rights reserved.